2022
DOI: 10.3390/ijerph192013141
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Attentional Processes in Outdoor and Indoor Environments: The Role of Physiological Self-Regulation

Abstract: Previous research has documented that exposure to green spaces has the beneficial effects of attention restoration and stress reduction. This study investigated the effects of indoor (classroom) and outdoor (green school garden) environments on attentional processes in interaction with emotion and physiological self-regulation. Children in third and fourth grades (n = 42) completed a school-related emotional Stroop task assessing the effects of outdoor and indoor classroom backgrounds when facing positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Interestingly, children’s self-reported emotional difficulties moderated the relationship between the environment and attentional performance. Students with higher self-reported emotional difficulties were those who benefitted more from a lesson in the greenness, an outcome that suggests how a calmer and quieter context for a lesson supports selective attention [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, children’s self-reported emotional difficulties moderated the relationship between the environment and attentional performance. Students with higher self-reported emotional difficulties were those who benefitted more from a lesson in the greenness, an outcome that suggests how a calmer and quieter context for a lesson supports selective attention [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to this, studies indicated the positive role of urban neighborhood green space in children’s emotional resilience [ 11 ]. Research has also shown that children were less distracted from negative emotional materials when presented with outdoor than indoor background stimuli [ 49 ]. Students with higher or lower emotional difficulties may therefore benefit from exposure to nature differently.…”
Section: Introductionmentioning
confidence: 99%